Statistical user interfaces - Sigbert Klinke (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
A statistical user interface is an interface between a human user and a statistical software package. Whenever we use a statistical software package we want to solve a specific statistical problem. But very often at first it is necessary to learn specific things about the software package. Everyone of us knows about the ?religious wars? concerning the question which statistical software package/method is the best for a certain task; see Marron (1996) and Cleveland and Loader (1996) and related internet discussions. Experienced statisticians use a bunch of different statistical software packages rather than a single one; although all of the major companies (at least the marketing departments) tell us that we only need their software package.
Keywords: 330